SP1-induced lncRNA DUBR promotes stemness and oxaliplatin resistance of hepatocellular carcinoma via E2F1-CIP2A feedback. (1st March 2022) - Liu, S; Bu, Xy; Kan, Anna; Luo, L; Xu, Yj; Chen, Hl; Lin, Xj; Lai, Zc; Wen, Ds; Huang, Lc; Shi, M
Abstract: Oxaliplatin-based chemotherapy is widely used to treat advanced hepatocellular carcinoma (HCC), but many patients develop drug resistance that leads to tumor recurrence. Cancer stem cells (CSCs) are known to contribute to chemoresistance, the underlying mechanism, however, remains largely unknown. In this study, we discovered a specificity protein 1 (SP1)-induced long noncoding RNA——DPPA2 upstream binding RNA (DUBR) and its high expression in HCC tissues and liver CSCs. DUBR was associated with HCC progression and poor chemotherapy response. Moreover, DUBR facilitated the stemness and oxaliplatin resistance of HCC in vitro and in vivo . Mechanistically, DUBR upregulated cancerous inhibitor of protein phosphatase 2A (CIP2A) expression through E2F1-mediated transcription regulation. DUBR also exerted function by binding microRNA (miR)-520d-5p as a competing endogenous RNA to upregulate CIP2A at mRNA level. CIP2A, in turn, stabilized E2F1 protein and activated the Notch1 signaling pathway, thereby increasing the stemness feature of HCC and leading to chemoresistance. In conclusion, we identified SP1/DUBR/E2F1–CIP2A as a critical axis to activate the Notch1 signaling pathway and promote stemness and chemoresistance of HCC. Therefore, DUBR could be a potential target in HCC treatment. Highlights: SP1-induced DUBR promotes stemness and drug resistance of hepatocellular carcinoma. DUBR functions by interacting with E2F1 and serving as competitive endogenous RNA. DUBR promotes stemness and drug resistance through Notch1 signaling pathway. DUBR/E2F1/CIP2A feedback contributes to stemness maintenance and drug resistance.